Green Energy: Problems and Prospects (International Journal of Psychosocial Rehabilitation, 2020)
In the current scenario, there is a growing concern about pollution caused by the production of energy through fossil fuels. Also, the natural resources (fossil fuels) are getting scarcer day by day, and there is a need to search for alternative sources of energy. It is at this point the concept of renewable energy receives more attention. Increasing population, technological revolution, and ever-rising demand for transportation are all challenges that we have to face. We must switch over to renewable sources of energy as a strategy for sustainable development. Our methodology consisted of reviewing the existing legal framework, conducting case studies, and providing suggestions and solutions. In conclusion, we point out the challenges faced in this transition to e-vehicles. Experts are skeptical over the possibility of evolving a customer-friendly economy. Budgetary provisions and financial subsidies are the need of the day. It is heartening to note that the state of Kerala is on a mission to create a modern transport e-system in a phased manner.